Exploring neuroendocrine carcinoma of the cervix: a case report and literature review - Gupta, Sumedha; Kalwaniya, Dheer Singh; Motwani, Varsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Neuroendocrine neoplasms (NENs) are rare, comprising less than 1% of cervical malignancies. Diagnosis and management of cervical neuroendocrine carcinoma (NEC) pose challenges due to its rarity and aggressive nature. Aim of the study was to highlight the importance of considering NEC in the differential diagnosis of cervical malignancies and underscore the potential benefits of comprehensive treatment approaches. We report a case of a 35-year-old woman presenting with post-coital bleeding, subsequently evaluated and diagnosed with NEC T1b1N0Mx following radical hysterectomy. Adjuvant chemoradiotherapy and chemotherapy led to one year of remission. Cervical NEC poses diagnostic and therapeutic challenges due to its rarity and aggressive nature. Despite multimodal treatment, prognosis remains poor, warranting further research and targeted therapies. The rarity of cervical NEC emphasizes the need for increased awareness among clinicians to facilitate early detection and appropriate management. Further studies are warranted to explore novel treatment modalities and improve outcomes for patients with this challenging malignancy.